Analisis Produk Kaos Oblong untuk Meminimalisir Defect dengan Metode New Seven Tools di Konveksi Graha Konveksindo - Pardosi, Adhe Rebeka; Sumiati, Sumiati (BRILIANT: Jurnal Riset dan Konseptual, 2024)
: Graha Konveksindo is a company that operates in the garment industry, where one of the products produced by this company is T-shirts. The aim of this research is to minimize defects by providing recommendations for improvements to T-shirts. This research was carried out using the New Seven Tools method, where this method can identify and find out the causes of defects in T-shirts and provide recommendations for improvement. The recommendations for improvement given are establishing clear procedures and standard standards for measuring color materials and attaching them to the coloring area, increasing cooperation with raw material suppliers who are reliable and provide high quality materials, checking raw material measurements and checking machine conditions. mixer before the production process, using an inspection checklist to ensure that each inspection step has been carried out correctly.